Improved gap-filling of eddy covariance CO 2 fluxes using remote sensing and environmental variables via XGBoost - Simon De Cannière; Sebastian Wieneke; Thomas Servotte; Adrià Descals; Tim Verdonck; Ivan Janssens (Agricultural and Forest Meteorology, 2026)

Contribution of dissolved organic carbon to total alkalinity in Enhanced Weathering experiments - Lukas Rieder; Mathilde Hagens; Reinaldy Poetra; Alix Vidal; Tullia Calogiuri; Anna Neubeck; Abhijeet Singh; Thomas Corbett; Harun Niron; Sara Vicca; Siegfried E. Vlaeminck; Iris Janssens; et al. (Applied Geochemistry, 2026)

Root and mycorrhizal contributions to soil organic carbon changes following 12 years of poplar coppice on former cropland and grassland - Gonzalo Berhongaray; Ivan A. Janssens; M. Francesca Cotrufo; Tim De Meulder; Marilyn Roland; Reinhart Ceulemans (Plant and Soil, 2026)
Background and Aims The establishment of bioenergy plantations as short-rotation coppice poplar systems has been proposed as a sustainable strategy to mitigate climate change through carbon capture. This study evaluates changes in soil organic carbon (SOC) after 12 years of poplar cultivation on former cropland and grassland in Belgium using repeated soil sampling to assess SOC stock changes and in-growth cores to identify carbon input pathways. Methods Using isotope tracing and in-growth cores with treatments excluding roots, mycorrhizae and above-ground inputs, we quantified the contributions of roots, mycorrhizae, and dissolved organic matter to new SOC formation and their interaction with the mineralization of native SOC. Results Results showed a significant increase in SOC in former croplands while grasslands experienced a slight SOC reduction, highlighting the influence of previous land use on SOC accrual potential. Root-derived inputs surpassed mycorrhizal contributions to SOC formation although both played a role in achieving a positive SOC balance. Conclusion This study underscores the critical role of roots in SOC accumulation and the importance of initial soil conditions when designing SOC accrual strategies through bioenergy plantations.

Multispecies grasslands sustain on-farm forage productivity and quality while reducing nitrogen fertilizer inputs - Bobby Zetterlind; Pedro Janssen; Rob Geerts; Tim Visser; Anthonie Stip; Marie Jasmijn Zwetsloot; Ellis Hoffland; Nick van Eekeren (Plant and Soil, 2025)
Aims Species-rich grasslands are proposed to promote biodiversity and reduce nitrogen (N) fertilization while maintaining productivity. However, the effectiveness of this strategy remains uncertain, particularly since grasslands with varying species richness are managed differently. We compared biomass yield and forage quality of three grassland management types varying in species richness and N fertilization levels in an on-farm context. Methods We compared biomass yield and forage quality of three grassland management types: permanent grassland ( Lolium perenne L. dominated) and multispecies grassland (sown with grasses, forbs, and legumes) fertilized with 0, 150, and 300 kg N ha⁻ 1 , and unfertilized semi-natural grassland (highly species-diverse) at twelve farm locations over two years. Results Multispecies grasslands with 150 kg N ha⁻ 1 produced yields similar to permanent grasslands fertilized with 300 kg N ha⁻ 1 due to higher legume cover and biological N 2 fixation. Nitrogen fertilization negatively impacted legume cover and likely reduced biological N 2 fixation. Multispecies grassland differed less in in terms of yield over two years with varying weather conditions, suggesting enhanced drought tolerance. Semi-natural grasslands had the highest species richness but the lowest biomass yields and forage quality. Conclusions Transitioning from permanent- to multispecies grasslands presents a promising diversification strategy for livestock farmers aiming to improve sustainability and biodiversity, while reducing N fertilization and maintaining productivity. Yet, species richness remains substantially higher in semi-natural grasslands at the cost of reduced biomass yield and forage quality. Optimization of N fertilization should be considered to improve persistence of legumes and forbs in agricultural multispecies grasslands.

Modulation of the xanthophyll cycle improves biomass productivity and light tolerance of the microalga Nannochloropsis oceanica - Tim Michelberger; Eleonora Mezzadrelli; Britt Rietbroek; Sarah D'Adamo; Giorgio Perin; Marcel Janssen; Tomas Morosinotto (Algal Research, 2025)

Metastasis-directed stereotactic radiotherapy in patients with breast cancer: results of an international multicenter cohort study - Alexander Fabian; Daniel Buergy; Fabian Weykamp; Juliane Hörner-Rieber; Denise Bernhardt; Judit Boda-Heggemann; Montserrat Pazos; Nora Mehrhof; David Kaul; Alicia S. Bicu; Eugenia Vlaskou Badra; Susanne Rogers; et al. (Clinical & Experimental Metastasis, 2025)
Metastasis-directed therapy (MDT) for oligometastatic breast cancer (≤ 5 metastases) has shown little effect in specific scenarios of randomized trials. Therefore, we aimed to assess outcomes after metastasis-directed stereotactic radiotherapy (SRT) in various clinical scenarios. We conducted an international retrospective cohort study in thirteen centers including breast cancer patients receiving SRT to any metastatic site. Outcomes included local recurrence (LR), progression-free survival (PFS), and overall survival (OS). Cumulative incidence analysis was used for LR, Kaplan–Meier estimates for PFS and OS. Covariables included patient, disease, and SRT characteristics. We performed univariable and multivariable analyses (MVA). Among 444 patients, 751 metastases were treated with SRT. Of these, 73% were intracranial and 27% extracranial lesions. Oligometastatic disease (OMD) was present in 66% of the patients. LR after two years occurred significantly more often in intracranial (25%) versus extracranial lesions (7%). In MVA of patients with OMD treated for intracranial sites, higher performance status was significantly associated with longer PFS. Further, higher performance status, biologic subtype (HR-pos./HER2-pos.), and MDT to all sites were significantly associated with longer OS. In MVA of oligometastatic patients treated for extracranial sites, biologic subtype (HR-neg./HER2-pos.) and synchronous metastasis were associated with significantly longer PFS, whereas higher grading was associated with significantly shorter PFS. Moreover, biologic subtype (HR-neg./HER2-neg.) was associated with significantly shorter OS. In conclusion, the role of MDT for breast cancer may vary per clinical scenario. Patients with OMD treated for intracranial lesions who had MDT to all sites showed superior OS. Our results should be validated prospectively.

Disturbance from tillage is a dominant factor in explaining differences in soil biodiversity of three grasslands management types - Nick van Eekeren; Jurre Dekker; Rob Geerts; Pedro Janssen; Anthonie Stip; Tim Visser; Jaap Bloem; Ron de Goede (Applied Soil Ecology, 2025)

How earthworms thrive and drive silicate rock weathering in an artificial organo-mineral system - Tullia Calogiuri; Iris Janssens; Alix Vidal; Jan Willem Van Groenigen; Tim Verdonck; Thomas Corbett; Jens Hartmann; Anna Neubeck; Harun Niron; Reinaldy P. Poetra; Lukas Rieder; Thomas Servotte; et al. (Applied Geochemistry, 2025)

Time series modelling for wastewater-based epidemiology of COVID-19: A nationwide study in 40 wastewater treatment plants of Belgium, February 2021 to June 2022 - Xander Bertels; Sven Hanoteaux; Raphael Janssens; Hadrien Maloux; Bavo Verhaegen; Peter Delputte; Tim Boogaerts; Alexander L.N. van Nuijs; Delphine Brogna; Catherine Linard; Jonathan Marescaux; Christian Didy; et al. (Science of The Total Environment, 2023)

Feasibility of Microlearning for Improving the Self-Efficacy of Cancer Patients Managing Side Effects of Chemotherapy - Anna Janssen; Kavisha Shah; Melanie Rabbets; Adnan Nagrial; Christopher Pene; Clare Zachulski; Jane L. Phillips; Paul Harnett; Tim Shaw (Journal of Cancer Education, 2023)
Lung cancer patients have a high symptom burden that negatively affects their quality of life. Increasing patient self-efficacy to deal with treatment side effects can ameliorate their symptom burden. Education programs can help enhance patient self-efficacy by giving patients more control over their condition through increased disease literacy. This study aimed to evaluate the feasibility of microlearning for delivering lung cancer patients’ information on side effects of chemotherapy. Secondary objectives of the program are to understand the acceptability of microlearning for delivery this type of education to lung cancer patients and the potential impact of microlearning on patient self-efficacy, knowledge and confidence managing side effects of chemotherapy. A mixed-methods prepost test (or quasi-experimental) study design was used to better enable patients to identify and manage the side effects of their condition and chemotherapy. Participants were patients diagnosed with stage II to stage IV lung cancer, who had a life expectancy of greater than 3 months and were aged 18 years or older. Multiple validated scales were used to assess patient self-efficacy pre- and post-intervention. The online program was evaluated using quantitative data of completion rates extracted from the online platform. Semi-structured interviews were used to explore the impact of the online program on perceived self-efficacy and quality of life. Twenty-three participants agreed to participate in the study and five agreed to complete a semi-structured interview. Participants found the content comprehensive, relevant and engaging. The program improved perceived disease literacy and helped participants develop coping strategies to manage side effects. Participants also found the platform easy to use and navigate. Additional courses and features were requested. Patients with a diagnosis of cancer receive a large amount of information about the side effects of chemotherapy and how to manage them. This information is often provided soon after diagnosis or upon commencement of therapy, which can be overwhelming for some patients. Microlearning, a method of online learning that spaces distributing of content over several weeks, may be a useful tool for supporting delivering of health information to this group of patients.

Long-term warming-induced trophic downgrading in the soil microbial food web - Mathilde Borg Dahl; Andrea Söllinger; Páll Sigurðsson; Ivan Janssens; Josep Peñuelas; Bjarni D. Sigurdsson; Andreas Richter; Alexander Tveit; Tim Urich (Soil Biology and Biochemistry, 2023)

Conflict analysis between commercial fisheries and common bottlenose dolphin ( Tursiops truncatus ) in the Dodecanese region, Greece - Sanne Eline Janssen; Julie Le Coz; Laura Macrina; Tim Grandjean; Anastasia Miliou (Fisheries Management and Ecology, 2022)
Increasing depletion of fish stocks in the Mediterranean Sea intensifies conflicts between fisheries and marine mammals, such as the common bottlenose dolphin ( Tursiops truncatus , Montagu, 1821). To increase the knowledge of such interactions in the eastern Mediterranean Sea, fishing activities of commercial fisheries and biomass of fish families targeted by fisheries and T. truncatus were analysed to identify areas that are more likely to be affected by these conflicts in the Dodecanese region of Greece. The area with the highest risk of conflict is located between Kos and Leros islands and the southwest coast of Turkey, which is mainly caused by trawl fishing activities. The presence of Sparidae, Merlucciidae, Mullidae and other unspecified fish families increased the likelihood of conflicts. Our applied method and results can be used to improve fishing regulations and management to diminish similar conflicts elsewhere in the world.

ESO-ESSO-ESTRO Multidisciplinary Course in Oncology for Medical Students: 4 Years of Experience (2016–2019) - Nicholas Pavlidis; Radoslaw Madry; Marc Peeters; Sergio Sandrucci; Janina Markowska; Fedro Peccatori; Alberto Costa; Jesper Grau Eriksen; Umberto Ricardi; Richard Poetter; Drisk Schrijvers; Jan B. Vermorken; et al. (Journal of Cancer Education, 2022)

Waves and Swells in High Wind and Extreme Fetches, Measurements in the Southern Ocean - Alexander V. Babanin; W. Erick Rogers; Ricardo de Camargo; Martin Doble; Tom Durrant; Kirill Filchuk; Kevin Ewans; Mark Hemer; Tim Janssen; Boris Kelly-Gerreyn; Keith Machutchon; Peter McComb; et al. (Frontiers in Marine Science, 2019)

Absence of CCL2 and CCL3 Ameliorates Central Nervous System Grey Matter But Not White Matter Demyelination in the Presence of an Intact Blood–Brain Barrier - Katharina Janssen; Mira Rickert; Tim Clarner; Cordian Beyer; Markus Kipp (Molecular Neurobiology, 2016)

Antenna size reduction as a strategy to increase biomass productivity: a great potential not yet realized - Tim de Mooij; Marcel Janssen; Oscar Cerezo-Chinarro; Jan H. Mussgnug; Olaf Kruse; Matteo Ballottari; Roberto Bassi; Sandrine Bujaldon; Francis-André Wollman; René H. Wijffels (Journal of Applied Phycology, 2015)

Short-Term Cuprizone Feeding Verifies N-Acetylaspartate Quantification as a Marker of Neurodegeneration - Barbara Maria Krauspe; Wolfgang Dreher; Cordian Beyer; Werner Baumgartner; Bernd Denecke; Katharina Janssen; Claus-Dieter Langhans; Tim Clarner; Markus Kipp (Journal of Molecular Neuroscience, 2015)

Mysid crustaceans as standard models for the screening and testing of endocrine-disrupting chemicals - Tim Verslycke; An Ghekiere; Sandy Raimondo; Colin Janssen (Ecotoxicology, 2007)